A Surveillance of invasive Streptococcus pneumoniae in Argentina 1994-2007: Changes in serotype distribution , serotype coverage of pneumococcal conjugate vaccine and antibiotic resistance - Ruvinsky, Raúl (2010)
Fil: Ruvinsky, Raúl. Hospital Carlos G. Durand; Buenos Aires, Argentina.